MULTIPLE SCATTERING OF ULTRASONIC WAVES BY SYSTEM OF 3D DEFECTS OF CANONICAL FORM (THEORY AND EXPERIMENT) - Nikolay V. Boyev; Khaled Mohamed El-Morabie; Vladimir A. Vdovin; Vladimir V. Zotov (Advanced Engineering Research)
The deterministic model of the defect distribution is described. The comparative analysis of the theoretical calculation and test data of the ultrasonic wave multireflection on the system of three cylindrical defects located in the finite-size elastic body is made.